STRUCTURAL CHARACTERIZATION OF FRACTIONATED GLYCOLIPID BIOSURFACTANTS SYNTHESIZED BY Pseudozyma aphidis YB205 - Sari, Martha; Kartika, I Made; Kusharyoto, Wien (Teknologi Indonesia, 2016)
Fractionation and structural characterization of glycolipid biosurfactant produced by yeast Pseudozyma aphidis strain YB205 was conducted. The yeast strain was grown in a nutrient broth with crude oil as the carbon sources and the glycolipid biosurfactant produced was isolated. The crude glycolipid was fractionated using column chromatography followed by complete separation and purification using extraction technique employing  different organic solvents. The fractions were subjected to activity test using oil displacement assay followed by chemical identity test using thin layer chromatography. In order to elucidate its chemical structure, the most active fraction was subjected NMR and FTIR analysis. Results showed that six major fractions were generated all of which showed biosurfactant activity. Four fractions is fractions 2, 4, 5, and 6 showed glycolipid characteristics and fraction 6 showed the highest biosurfactant activity. Combination of NMR and FTIR spectroscopy spectra indicated that chemical structures of fraction 6 belonged to glycolipid species.